Application of SYBR Green Real-Time PCR for Detection of Toxigenic Vibrio cholerae O1 in the Aquatic Environment - Aschana Tirapattanun (Science Faculty of Chiang Mai University, 2019)
Vibrio cholerae O1 is the causative agent of cholera disease and its natural habitat is the aquatic environment. V. cholerae can become a \viable but non-culturable\ (VBNC) organism resulting in unsuccessful isolation from aquatic environments; therefore, sensitive, rapid and accurate detection of VBNC taken from an aquatic environment is needed. The aim of this study was to develop real-time SYBR green PCR compared to the conventional PCR and culture methods for detection of V. cholerae O1 in water samples. The SYBR green real-time PCR assays were developed using specific primers targeting genes for the outer membrane protein (ompW), cholera toxin A (ctxA), rfbO1 (serogroup O1) and rfbO139 (serogroup O139). The respective sensitivity of uniplex (ompW, rfbO139) and duplex (ctxA and rfbO1) SYBR green real-time PCR was 102 CFU/ml (3 CFU/PCR reaction) and 103 CFU/ml (25 CFU/PCR reaction). V. cholerae O1 was detected in 31.8% (27/85) of samples and all were ctxA positive by SYBR green real-time PCR and conventional PCR, vs. 3.5% (3/85 samples) by culture method. Our results indicate that both PCR-based assays have similar efficiency for detecting ompW, ctxA, rfbO1 and rfbO139 genes and could be applied for rapid detection of V. cholerae O1 in environmental water samples.